ANALYSIS OF THE IMPACT OF THE FLOOD DISASTER ON THE EXISTENCE OF COMMUNITY SOCIO-ECONOMIC LIFE - bakar, abu (Jurnal Sosial Humaniora, 2024)
Floods greatly affect socio-economic activities. The number of heads of families affected by the floods was 6,460 heads of families, the number of souls was 19,380 people, 6,460 houses/buildings and the number that was evacuated was 1,239 heads of families and 4,555 people. Flood disaster is an event that threatens and disrupts people’s lives and livelihoods. Disasters can be caused both by natural factors and non-natural factors (human activities) resulting in loss of life, environmental damage, loss of property, and psychological impacts. The purpose of this study is to explain the socio-economic conditions of the people in Makassar City; Analyze the factors that cause flooding in Kita Makassar; Identify the evacuation of communities affected by floods. This study uses a cross-sectional design. The approach to this research is "collaborative" which is a form of disaster management that is more of a public institution directly collectively. The samples taken were 99 people. Data consists of primary and secondary. Data collection techniques are observation, interviews, literature studies and documentation. Data analysis uses public perception, Likert scale, Weight Mein Score and correlation. The results showed that the increasing number of companies reached 14,584 business units consisting of 1,460 large trades, 5,550 medium trades, and 7,574 small trades. There are 143 industrial businesses classified as large and medium which accommodate 17,767 workers. Factors that cause floods are: The Effect of Rainfall, Changes in Land Allotment in watersheds, Effects of Surface Elevation, and People Disposing of Garbage. In Makassar City there were no evacuation sites, so the people were evacuated to residents’ homes, mosques and posyandu. As many as 50 respondents were evacuated at residents’ homes, 30 respondents were evacuated at Posyandu and 19 respondents were evacuated at the mosque.